Searching for Work with a Criminal Record. (6th May 2019) - Smith, Sandra Susan; Broege, Nora C R
Abstract: People with a criminal record face substantial demand-side employment barriers that have clear implications for whether or not they search for work and what strategies they use. We know relatively little, however, about whether and how penal contact affects patterns of job search and how search patterns affect search success. Using the 2001–2011 waves of the 1997 cohort of the National Longitudinal Survey of Youth (NLSY97), we find that penal contact and penal dispositions—arrest, conviction, and incarceration—reduce odds of job search, decrease the number of search methods job seekers deploy, and direct job seekers away from search methods that are generally more efficient and effective at yielding offers. Further, altered search patterns contribute significantly to post-contact job seekers' lower odds of search success, especially for blacks. Taken together, our findings suggest that job search engagement is another key mechanism linking penal contact and poorer job search outcomes.